IMPLEMENTASI MODEL PROBLEM BASED LEARNING (PBL) TERHADAP KETERAMPILAN BERKOLABORASI DAN PENGUASAAN KONSEP SISTEM PERNAPASAN MANUSIA PADA KURIKULUM MERDEKA DI SMPN 2 HULU SUNGKAI - Nilawati; Agus Sujarwanta; Dasrieny Pratiwi (Prodi Pendidikan Biologi FKIP Universitas Muhammadiyah Metro, 2026)
The demands of 21st-century education require students to develop strong collaboration skills. However, students at SMPN 2 Hulu Sungkai demonstrated relatively low collaboration skills, which were attributed to teacher-centered learning practices. This study investigated the effectiveness of Problem-Based Learning (PBL) within the Independent Curriculum in improving students’ collaboration skills and mastery of the Human Respiratory System concept. A quantitative approach with a quasi-experimental nonequivalent control group design was employed. The sample consisted of two Grade VIII classes (25 students each), purposively selected based on similar pretest achievement and randomly assigned as the experimental and control groups. Both groups completed pretests and posttests, while the experimental group received PBL instruction and the control group received conventional teaching. Data were analyzed using an independent-samples t-test. The results revealed that PBL significantly improved students’ collaboration skills, with the experimental group achieving a mean score of 4.16 (83.2%) compared with 3.00 (60.0%) in the control group (t = 5.658 > 1.677). PBL also significantly enhanced students’ mastery of the Human Respiratory System concept, as indicated by a higher posttest mean score in the experimental group (75.4; 84.0%) than in the control group (71.2; 72.0%) (t = 1.787 > 1.677). These findings indicate that authentic problem-solving activities in PBL promote active participation, collaborative learning, and meaningful conceptual understanding. Therefore, integrating PBL into science instruction is recommended to foster students' collaboration skills and conceptual mastery.